Morphological and functional aspects of progenitors perturbed in cortical malformations - Bizzotto, Sara; Francis, Fiona (Frontiers in Cellular Neuroscience, 2015)
In this review, we discuss molecular and cellular mechanisms important for the function of neuronal progenitors during development, revealed by their perturbation in different cortical malformations. We focus on a class of neuronal progenitors, radial glial cells (RGCs), which are renowned for their unique morphological and behavioural characteristics, constituting a key element during the development of the mammalian cerebral cortex. We describe how the particular morphology of these cells is related to their roles in the orchestration of cortical development and their influence on other progenitor types and post-mitotic neurons. Important for disease mechanisms, we overview what is currently known about RGC cellular components, cytoskeletal mechanisms, signalling pathways and cell cycle characteristics, focusing on how defects lead to abnormal development and cortical malformation phenotypes. The multiple recent entry points from human genetics and animal models are contributing to our understanding of this important cell type. Combining data from phenotypes in the mouse reveals molecules which potentially act in common pathways. Going beyond this, we discuss future directions that may provide new data in this expanding area.